Utilization of the DJI Phantom 3 Advance Quadcopter Type Drone Vehicle for Area Mapping of the Samarinda State Agricultural Polytechnic Campus - Dyah Widyasasi; Dwi Agung Pramono; Hasanudin Hasanudin; Dwinita Aquastini; Emi Malaysia; Rudi Djatmiko (Jurnal Loupe, 2024)
This research is motivated by the fact that currently remote sensing technology continues to develop, both in terms of data collection and processing. This is characterized by the existence of data collection techniques using unmanned aerial vehicles for aerial photo mapping. The advantage of using this technology is that it is effective and efficient both in terms of time and human resources for mapping in areas that are not too large. Another advantage is that it can produce clearer photos, because the plane's flying height is below 400 meters above ground level so that during the shooting process there is no cloud interference. The aim of this research is to create an aerial photo map at the Samarinda State Agricultural Polytechnic, validate objects in aerial photos and in the field, and provide information about the area, boundaries and topography of the Samarinda State Agricultural Polytechnic campus area. The implementation of activities and research objects is the Samarinda State Agricultural Polytechnic campus area. This research uses a small format aerial photo mapping method using a Quadcopter, making it easier to determine where to start taking off and landing. With a Quadcopter vehicle, grounding problems are no longer an obstacle. The research results showed that photography carried out with a Quadcopter at a height of 200 m above the ground produced an area of 28.17 Ha and a spatial resolution of 8.40 cm/pixel. The validation results in aerial photos and in the field using drones have a small difference between 0-4 cm with an average of 1.625 cm/photo. From the digitization results of campus objects, there are 30 objects on campus with a total area of 2.67 Ha. As for the topography results in the campus area, the highest point is 107.5 meters above sea level and the lowest point is 60 meters above sea level.